INTRODUCTION TO BASIC MICROBIOLOGY CONCEPTS IN THE PREVENTION OF INFECTIOUS DISEASES at YAPIM BIRU-BIRU PRIVATE HIGH SCHOOL - Fahdi, Firdaus; Sari, Herviani (INSTITUT KESEHATAN DELI HUSADA, 2024)
Infectious diseases, caused by microorganisms such as viruses, bacteria, parasites, and fungi, pose a significant public health challenge, particularly in tropical countries like Indonesia. These microorganisms can exist harmlessly within the human body but may become pathogenic under certain conditions. Schools, due to their dense population and frequent interpersonal interactions, are potential hotspots for the transmission of infectious diseases. The lack of awareness about pathogenic microorganisms and simple hygiene measures often exacerbates the spread of preventable infections. To address this, a community engagement program was conducted at YAPIM Biru-Biru Private Senior High School/Vocational School to enhance students' understanding of microbiology and its role in preventing infectious diseases. The objectives included increasing awareness about pathogenic microorganisms, educating on the importance of environmental hygiene, and teaching simple preventive measures to reduce infection risks in school settings. The program involved three phases: preparation, implementation, and feedback. Activities included a pre-test to assess baseline knowledge, a presentation on basic microbiology concepts, a post-test to eval_uate learning outcomes, and a Q&A session to reinforce understanding. The results showed improved participant knowledge, behavioral changes such as frequent handwashing and mask usage when unwell, and positive responses from participants, indicating the program's success. This initiative highlights the importance of regular educational programs to foster consistent hygiene practices and prevent infectious diseases in schools.